1946
DOI: 10.1103/physrev.70.219
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity of Sodium-Ammonia Solutions

Abstract: has reported the occurrence of superconductivity in quickly frozen solutions of sodium in ammonia. In view of the fact that all other superconductors have transition points of the order of 5°K, corresponding to an excitation energy of 5X10~4 ev, the appearance of superconductivity at very much higher temperatures (about 200°K) is somewhat unexpected.We have repeated Ogg's conductivity experiment on a number of concentrations ranging from 0.7N to 2N and noted in agreement with his work that the resistance drops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1947
1947
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…A similar relation had already been obtained for the helium film by Bijl, de Boer and AIichels (1941) and by Gogate and Rai (1944). Daunt and Mendelssohn (1946a) have pointed out that this relation appears to be a direct consequence of a diffusion of the superfluid constituent under its zero point momentum. An experiment designed to prove the existence of such a mechanism has given a positive result (Daunt and Mendelssohn I946 b).…”
Section: ;supporting
confidence: 78%
See 1 more Smart Citation
“…A similar relation had already been obtained for the helium film by Bijl, de Boer and AIichels (1941) and by Gogate and Rai (1944). Daunt and Mendelssohn (1946a) have pointed out that this relation appears to be a direct consequence of a diffusion of the superfluid constituent under its zero point momentum. An experiment designed to prove the existence of such a mechanism has given a positive result (Daunt and Mendelssohn I946 b).…”
Section: ;supporting
confidence: 78%
“…I n the latter type of experiment the film flow is always limited by this critical rate which, on the other hand, is independent of the level difference. I n order to determine the differencein gravitational potential at the ends of the film, Daunt and Mendelssohn (1946b) employed a device in which the flow occurred at less than the critical rate, Under these conditions it was found that within the limit of accuracy the potential difference at the ends was zero; it was less than 15 times smaller than the level difference required to accelerate the helium to the observed velocity by free fall. -4tkins (1948) has found a film flow of a higher rate than that previously observed ; this also depended on the liquid level when, instead of a beaker, a bulb with a narrow neck was used.…”
Section: ;mentioning
confidence: 99%
“…The Ðrst to report on an apparent superconductivity was Ogg,2 who observed long-lasting ring currents in the classical Kamerlingh Onnes experiment with frozen MAS. The e †ect was subsequently conÐrmed by Hodgins3 and Verkin et al,4 but could not be reproduced by Boorse et al, 5 Daunt et al 6 and Giulotto and Gigli. 7 No evidence of Ñux expulsion or of truly persistent currents was obtained.…”
Section: Introductionmentioning
confidence: 94%
“…1 A graybody comparison, in the spectral region occupied by the band, approximately 9 mu to 10 mu, is then made between the radiation intensity of the earth's surface (thermocouple) to space and the return radiation intensity of the ozone layer. 1 The method is a promising one, for even the preliminary, very low resolution spectra yield essentially correct temperatures. The temperature of the ozone layer is found to be -44°C and -53°C for the evenings of September 5, 1941 and November 3, 1941, respectively-8…”
mentioning
confidence: 99%